On the basis of source: Impacts of individual differences on multiple-document integrated reading and writing tasks. (June 2022) - McCarthy, Kathryn S.; Yan, Eleanor F.; Allen, Laura K.; Sonia, Allison N.; Magliano, Joseph P.; McNamara, Danielle S.
Abstract: Few studies have explored how general skills in both reading and writing influence performance on integrated, source-based writing. The goal of the present study was to consider the relative contributions of reading and writing ability on multiple-document integrative reading and writing tasks. Students in the U.S. (n = 94) completed two tasks in which they read text sets about a socioscientific issue, generated constructed responses while reading, and then composed integrated essays. They also completed individual difference measures (general knowledge, reading skill, reading strategy use) and wrote independent essays to assess their writing ability. Mixed effect models revealed that general knowledge and reading skills contributed to integrated essay performance, but that once general writing ability was entered into the model, it became the strongest predictor of integrated writing scores. These results suggest the need for deeper consideration of the role of writing skills in integrated reading and writing tasks. Highlights: Students often engage in source-based, multiple-document integrated reading and writing tasks. Studies rarely measure the contribution of both reading and writing in integrated tasks. Academic knowledge, reading skills, and writing ability correlate with integrated essay score. However, only academic knowledge and writing ability predict integrated essay score. Educators needs to consider writing ability when using integrated writing as an outcome measure.